M/M/1 retrial queueing model with variable service rate - Bratiichuk, M. S.; Chechelnitsky , A. A.; Usar, I. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 519.21 The paper deals with queueing system of the type M/M/1 with repeated claims in the case where the service intensitydepends on the loading of the system, i.e., on the number of claims in the line to be served. We establish the existenceconditions and the formulas for ergodic distribution of the number of claims in the system with bounded and unboundedlines of repeated claims.